1993
DOI: 10.1017/s095252380001021x
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical compartmentation of monkey and human visual cortex: Similarities and variations in calbindin immunoreactivity across species

Abstract: The compartmental organization of visual cortical neurons was examined across species of primates by directly comparing the pattern of immunoreactivity for the 28-kD vitamin D-dependent calcium-binding protein (calbindin) in area 17 of squirrel monkeys, macaques, and neurologically normal adult humans. Area 17 of macaques and squirrel monkeys was similar in that somata and processes intensely immunoreactive for calbindin were present in the same layers (II-III, IVB, and V) and in both species formed a well-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
39
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 68 publications
11
39
1
Order By: Relevance
“…A similar distribution has been observed in the human temporal cortex (del Río and DeFelipe, 1997a). Other authors have reported uneven CB immunostaining in layer III of V1 in the macaque monkey, with the more intense staining observed present around the cytochrome oxidase-rich puffs in layer III (van Brederode et al, 1990;Hendry and Carder, 1993;Blü mcke et al, 1994;Carder et al, 1996). However, in our hands, comparison of alternate sections stained for CB and cytochrome oxidase (unpublished observations) revealed that the distribution of double-bouquet cell axons is unrelated to the pattern of cytochrome oxidase staining in layers II and III, a finding substantiated by Peters and Shetares (1997).…”
Section: Identification and Distribution Of Double-bouquet Cells And supporting
confidence: 78%
“…A similar distribution has been observed in the human temporal cortex (del Río and DeFelipe, 1997a). Other authors have reported uneven CB immunostaining in layer III of V1 in the macaque monkey, with the more intense staining observed present around the cytochrome oxidase-rich puffs in layer III (van Brederode et al, 1990;Hendry and Carder, 1993;Blü mcke et al, 1994;Carder et al, 1996). However, in our hands, comparison of alternate sections stained for CB and cytochrome oxidase (unpublished observations) revealed that the distribution of double-bouquet cell axons is unrelated to the pattern of cytochrome oxidase staining in layers II and III, a finding substantiated by Peters and Shetares (1997).…”
Section: Identification and Distribution Of Double-bouquet Cells And supporting
confidence: 78%
“…Future investigations can be expected to reveal additional human specializations of neural organization and function. Candidate specializations include several reported human-monkey differences (56)(57)(58)(59). As the present study illustrates, however (see also ref.…”
Section: Discussionsupporting
confidence: 60%
“…Because of the unbiased nature of the stereologic sampling design, these cell counts were not influenced by potential variation in interneuron densities among cytochrome oxidase (CO)-rich blobs, stripes, or non-CO-rich modules [Hendry and Carder, 1993]. Although most interneuron subtypes displayed statistically isometric scaling patterns against total neuron density, CB-ir interneuron subtypes were characterized by a positive allometric scaling relationship.…”
Section: Scaling Patterns Of Interneurons and Phylogenetic Variationmentioning
confidence: 99%